2021
DOI: 10.1111/ocr.12507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment effects from total arch distalization using modified C‐palatal plates versus maxillary premolar extraction in Class II patients with severe overjet

Abstract: Introduction This study aimed to compare the skeletodental and soft tissue changes with total arch distalization using a modified C‐palatal plate (MCPP) and maxillary first premolar extraction treatment in Class II malocclusion patients with severe overjet. Setting and sample population The sample consisted of 46 adult patients who had Class II Division 1 malocclusion with severe overjet; 25 of them received non‐extraction treatment with MCPPs (age, 22.5 ± 7.2 years), and 21 received maxillary first premolar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The plate group showed 4.33 mm of distalization of the maxillary rst molar, combined with 1.85 mm of intrusion and 3.10° of distal tipping. Previous studies also reported similar distalization, intrusion and distal tipping of U6 resulted by the application of MCPP in adults [22,38,40,[46][47][48]59].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The plate group showed 4.33 mm of distalization of the maxillary rst molar, combined with 1.85 mm of intrusion and 3.10° of distal tipping. Previous studies also reported similar distalization, intrusion and distal tipping of U6 resulted by the application of MCPP in adults [22,38,40,[46][47][48]59].…”
Section: Discussionmentioning
confidence: 60%
“…Recently, the use of the modi ed C-palatal plate (MCPP) for maxillary arch distalization has been reported for Class II corrections in both adolescents and adults [25,37]. MCPPs showed a signi cant distalization of the maxillary rst molars by about 1.65 to 5.4 mm with 0.28 to 4.36 degrees of distal tipping [22,38,47,[39][40][41][42][43][44][45][46]]. Lee et al, in a retrospective clinical study, compared the treatment effects between palatal and buccally placed TADs, and showed signi cantly greater amounts of distalization and intrusion with a smaller amount of distal tipping of the maxillary rst molars using the MCPP [22].…”
Section: Introductionmentioning
confidence: 99%
“…Alfawaz et al [ 37 ] compared the effect of total arch distalization versus maxillary premolar extraction in Class II patients. They reported no significant differences regarding all skeletal and soft tissue treatment effects except for the maxillary first molar positional changes which were highly significantly between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kook et al 16–21 introduced the modified C‐palatal plate (MCPP) to provide skeletal anchorage that avoids the disadvantages of extraoral anchorage, but it can interfere with the proper linguopalatal contact and sound production, yet there have been no reports on MCPP inducing speech disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, significant individual variations were reported in compensatory mechanisms to overcome palatal speech perturbation effects. 15 Recently, Kook et al [16][17][18][19][20][21] introduced the modified C-palatal plate (MCPP) to provide skeletal anchorage that avoids the disadvantages of extraoral anchorage, but it can interfere with the proper linguopalatal contact and sound production, yet there have been no reports on MCPP inducing speech disturbances.…”
mentioning
confidence: 99%